Bond strength of hard chairside reline resins to a rapid polymerizing denture base resin before and after thermal cycling Resistência de união de resinas rígidas para reembasamento imediato a resina para base de prótese de rápida polimerização antes e após termociclagem - Karin Hermana Neppelenbroek; Ana Cláudia Pavarina; Mauricio Neves Gomes; Ana Lucia Machado; Carlos Eduardo Vergani (University of São Paulo, 2006)
PURPOSE: This study assessed the shear bond strength of 4 hard chairside reline resins (Kooliner, Tokuso Rebase Fast, Duraliner II, Ufi Gel Hard) to a rapid polymerizing denture base resin (QC-20) processed using 2 polymerization cycles (A or B), before and after thermal cycling. MATERIALS AND METHODS: Cylinders (3.5 mm x 5.0 mm) of the reline resins were bonded to cylinders of QC-20 polymerized using cycle A (boiling water-20 minutes) or B (boiling water; remove heat-20 minutes; boiling water-20 minutes). For each reline resin/polymerization cycle combination, 10 specimens (groups CAt e CBt) were thermally cycled (5 and 55 ºC; dwell time 30 seconds; 2,000 cycles); the other 10 were tested without thermal cycling (groups CAwt ad CBwt). Shear bond tests (0.5 mm/min) were performed on the specimens and the failure mode was assessed. Data were analyzed by 3-way ANOVA and Newman-Keuls post-hoc test (alpha=.05). RESULTS: QC-20 resin demonstrated the lowest bond strengths among the reline materials (P<.05) and mainly failed cohesively. Overall, the bond strength of the hard chairside reline resins were similar (10.09±1.40 to 15.17±1.73 MPa) and most of the failures were adhesive/cohesive (mixed mode). However, Ufi Gel Hard bonded to QC-20 polymerized using cycle A and not thermally cycled showed the highest bond strength (P<.001). When Tokuso Rebase Fast and Duraliner II were bonded to QC-20 resin polymerized using cycle A, the bond strength was increased (P=.043) after thermal cycling. CONCLUSIONS: QC-20 displayed the lowest bond strength values in all groups. In general, the bond strengths of the hard chairside reline resins were comparable and not affected by polymerization cycle of QC-20 resin and thermal cycling. OBJETIVO: Esse estudo avaliou a resistência de união ao cisalhamento de 4 resinas rígidas para reembasamento imediato (Kooliner, Tokuso Rebase Fast, Duraliner II, Ufi Gel Hard) a uma resina para base de prótese de rápida polimerização (QC-20) submetida a 2 ciclos de polimerização (A e B), antes e após termociclagem. MATERIAIS E MÉTODOS: Cilindros (3,5 mm x 5,0 mm) das resinas reembasadoras foram unidas aos cilindros de resina QC-20 polimerizados pelo ciclo A (água fervente - 20 minutos) ou B (água fervente; remoção do calor-20 minutos; água fervente-20 minutos). Para cada combinação resina reembasadora/ciclo de polimerização, 10 corpos-de-prova (grupos CAt e CBt) foram termociclados (5 e 55 ºC; intervalo de tempo 30 segundos; 2.000 ciclos); os outros 10 foram testados sem termociclagem (grupos CAwt e CBwt). Os testes de resistência de união ao cisalhamento (0,5 mm/min) foram realizados sobre os corpos-de-prova e o tipo de falha avaliado. Os dados foram analisados por análise de variância (ANOVA) e teste de Newman-Keuls (alfa=0,05). RESULTADOS: A resina QC-20 demonstrou a menor resistência de união entre os materiais reembasadores (p<0,05) e apresentou falhas predominantemente coesivas. De modo geral, os valores de resistência de união das resinas rígidas para reembasamento imediato foram similares (10,09±1,40 a 15,17±1,73 MPa) e a maioria de falhas foram do tipo adesiva/coesiva (mista). Entretanto, a resina Ufi Gel Hard unida à resina QC-20 polimerizada pelo ciclo A e não termociclada apresentou a maior resistência de união (p<0,001). Quando as resinas Tokuso Rebase Fast e Duraliner II foram unidas à resina QC-20 polimerizada pelo ciclo A, a resistência de união aumentou (p=0,043) após a termociclagem. CONCLUSÕES: QC-20 apresentou os menores valores de resistência de união em todos os grupos. Em geral, os valores de resistência de união das resinas reembasadoras rígidas foram comparáveis e não foram influenciados pelo ciclo de polimerização da resina QC-20 e pela termociclagem.